Juridical Analysis of the Business Competition of Minimarket Franchises in Jayapura City - Krey, Thresia Hilda Mathelda Yenkase; Palit, Silvester Magnus Loogman; Senandi, Winna Amelia Alfrida (CV. Social Politic Genius (SIGn), 2025)
The massive expansion of minimarket franchises in Jayapura City triggers structural inequality, threatening the existence of local business actors, and thus demands a holistic synchronization of business competition law. This research aims to examine the synchronization of spatial planning and minimarket licensing zoning regulations, and to analyze the legal protection of construction through a partnership scheme based on Jayapura Municipal Regulation Number 10 of 2018. Utilising a normative juridical research method with a statutory and conceptual approach, this study examines the legal vagueness in regional regulations and the weakness of supervision of private law instruments. The analysis indicates that zoning enforcement operates suboptimally due to the limited coercive power of administrative sanctions, which corporations frequently view as mere operational risks. In the dimension of partnership protection, the phrase “prioritizing local merchants” in the regional regulation is identified as a vague norm that triggers tokenism and perpetuates the abuse of circumstances (misbruik van omstandigheden) in standard agreement drafts. In conclusion, legal protection for local merchants remains vulnerable due to the lack of integration between public spatial planning compliance and private contractual justice. Therefore, this research recommends the issuance of a Mayoral Regulation to stipulate a quantitative percentage for local product absorption in the People-Owned Stores program, and the establishment of a regional task force to audit and cancel exploitative business agreement clauses.